Yellow Pitahaya (Selenicereus megalanthus Haw.): The Less Known of the Pitahayas - Daniel Valero; Alex Erazo-Lara; María Emma García-Pastor; Pedro Antonio Padilla-González; Vicente Agulló; Fátima Badiche El-Hiali; María Serrano (Foods, 2025)
Pitahaya or dragon fruit is an exotic fruit native to Mesoamerica and is cultivated in several regions of the world. In recent years, pitahaya has become increasingly in demand, firstly, for its good nutritional and organoleptic qualities and, secondly, for its richness in antioxidants and bioactive compounds. Spain has opted for new tropical crops, and among them, pitahaya is one of the most planted in recent years. Most of the investigations on pitahaya were conducted with red cultivars, while the research on yellow pitahaya (Selenicereus megalanthus Haw.) is very scarce. In this review, the current knowledge about types of pitahayas, the fruit growth and ripening, the quality attributes, the postharvest storage, the use of by-products, and the health attributes were covered.